(untitled) (FULafia Journal of Science and Technology, 2023)
The Research was carried out to assess the browse intake and nutrient digestibility of grazing West African Dwarf (WAD) goats fed varying levels of Gmelina arborea leaves as supplement. Which produces appreciable amount of forage even at the peak of the dry season in the tropics, thereby ensuring all year round supply of foliage and fodder. Thirty growing West Africa Dwarf (WAD) goats were used to determine the level of browse intake and nutrient digestibility by goats fed varying levels Gmelina arborea leaves as supplement The goats were randomly divided into five groups of six animal per group. Goats in Treatment A were fed commercial growers mash, at 0.50 kg, Treatment B were fed 0.25 kg of Gmelina arborea leaves, Treatment C were fed 0.50 kg of Gmelina arborea leaves, Treatment D 0.75 kg and Treatment E 1.00 kg of Gmelina arborea leaves